PENGARUH PEMASARAN RELASIONAL DAN LOYALITAS TERHADAP KEPUASAN NASABAH PT. BANK NEGARA INDONESIA (BNI) KANTOR CABANG MEDAN - Syafriadi (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2016)
PT. Bank Negara Indonesia established since 1946, BNI formerly known as Bank NegaraIndonesia, is the first bank formed and owned by the Government of Indonesia. Customersatisfaction can be created through marketing quality provided by the company to itscustomers. The better the quality of its services, the higher the customer loyalty to thecompany that will meciptakan customer satisfaction by itself. Hypothesis Test Resultsreasional marketing variables (X1) on customer satisfaction at the results obtainedrelational marketing job characteristics (X1) partially have a significant influence oncustomer kepauasan (Y) PT. Bank Negara Indonesia (Persero) Tbk Cabang Medan.obtained t value of 3.937 with a probability value t (Sig) is 0,000 (Sig. <α0,05). HypothesisTest Results loyalty variables on customer satisfaction in the results obtained Loyaltyvariable (X2) partially have a significant influence on customer kepauasan (Y) PT. BankNegara Indonesia (Persero) Tbk Cabang Medan .. obtained t value of 5,077 t with aprobability value (Sig) is 0,000 (Sig. <Α0,05). F count = 127.675 with a probability valueF (sig) is 0.000 (sig.0,000˂α0,05). Thus Ho rejected and Ha accepted. It can be concludedthat the relationship marketing (X1) and loyalty (X2) simultaneously have a significantinfluence on customer satisfaction (Y) PT Bank Negara Indonesia (Persero) Tbk, MedanBranch.